2008
DOI: 10.1136/jmg.2008.057653
|View full text |Cite
|
Sign up to set email alerts
|

Noonan and cardio-facio-cutaneous syndromes: two clinically and genetically overlapping disorders

Abstract: Taken together, our results indicate that the molecular and clinical overlap between CFC and NS is more complex than previously suggested and that the syndromes might even represent allelic disorders. Furthermore, we suggest that the diagnosis should be refined to, for example, NS-PTPN11-associated or CFC-BRAF-associated syndromes after the genetic defect has been established, as this may affect the prognosis and treatment of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 30 publications
5
84
0
Order By: Relevance
“…However, there are no sufficient histological data to rule out the possibility that early onset cardiomyopathies with hypertrophic appearances could have increased cardiomyocyte numbers. B-Raf +/LSLV600E mice do not develop other cardiovascular defects typically present in CFC patients, such as pulmonary valve stenosis, septal defects, and aortic abnormalities (12,24,25). Whether these differences are caused by the intrinsic physiological differences between the cardiovascular systems of rodents and humans or differences in the constitutive B-Raf kinase activity remains to be determined.…”
Section: B-raf +/Lslv600e Mice Display Craniofacial Dysmorphism and Dmentioning
confidence: 99%
“…However, there are no sufficient histological data to rule out the possibility that early onset cardiomyopathies with hypertrophic appearances could have increased cardiomyocyte numbers. B-Raf +/LSLV600E mice do not develop other cardiovascular defects typically present in CFC patients, such as pulmonary valve stenosis, septal defects, and aortic abnormalities (12,24,25). Whether these differences are caused by the intrinsic physiological differences between the cardiovascular systems of rodents and humans or differences in the constitutive B-Raf kinase activity remains to be determined.…”
Section: B-raf +/Lslv600e Mice Display Craniofacial Dysmorphism and Dmentioning
confidence: 99%
“…In our cohort, all mutations were found to affect exons 2 and 3 of both genes, confirming earlier observations indicating that the regulatory region and the adjacent N-terminal portion of the catalytic domain are mutation hot spots, possibly because of the specific perturbing effect of mutations on the autoinhibitory mechanism controlling protein activation. Nevertheless, based on the identification of rare mutations outside this region (E203Q in MEK1 18 and K273R in MEK2 3 ), MEK1 and MEK2 mutation screening should not be limited to these exons. Our data also confirmed that mutations affecting the tyrosine residue at codon 130 of MEK1 represent the most common event underlying CFCS, and that mutations involving residue F57 are the most frequent lesions occurring in MEK2.…”
Section: Discussionmentioning
confidence: 99%
“…On a related note, some studies have found that, occasionally, mutations in BRAF and MEK1 can result in a phenotype more similar to NS or NSML than to typical CFC (Nystrom et al 2008;Nishi et al 2015;Sarkozy et al 2009). This finding has resulted in some debate regarding whether these individuals can be diagnosed as having a Noonan-like syndrome or whether they simply exhibit a milder phenotype of CFC (Neri et al 2008).…”
Section: Relationship Between Genotype and Neurocognitive Outcomesmentioning
confidence: 99%
“…For example, individuals with KRAS mutations have been described as having an intermediate or ambiguous clinical phenotype that has features of both NS and CFC syndrome (Schubbert et al 2006;Nystrom et al 2008). Individuals with this mutation can be diagnosed with either one of these conditions depending on their specific clinical presentation.…”
Section: Relationship Between Genotype and Neurocognitive Outcomesmentioning
confidence: 99%